Is the Pelvis-Thorax Coordination a Valuable Outcome Instrument to Assess Patients With Hip Osteoarthritis? - Moissenet, Florent; Naaim, Alexandre; Ornetti, Paul; Bourredjem, Abderrahmane; Binquet, Christine; Morisset, Claire; Gouteron, Anais; Maillefert, Jean-Francis; Laroche, Davy (Frontiers in Bioengineering and Biotechnology, 2020)
Objective. The evaluation of the disease severity in hip osteoarthritis (OA) patients being currently based on subjective instruments. It would be of interest to develop more objective instruments, for example based on gait analysis. The aims of this study were to explore if pelvis-thorax coordination parameters could be valuable instrument outcomes to achieve this evaluation by assessing their reliability, discriminant capacity and responsiveness. Methods. Three groups of subjects; healthy, hip OA patients with severe disease (defined as indication to surgery), hip OA patients with less severe disease (no indication to surgery) were included. Hip OA patients with severe disease were evaluated before and 6 months after surgery. Subjects had to perform a gait analysis at comfortable speed, and pelvis-thorax coordination was evaluated. The correlations with clinical and structural parameters, as well as reliability, discriminant capacities and responsiveness, were assessed. Results. The pelvis-thorax coordination in the coronal plane during walking was correlated to clinical and to structural severity in hip OA patients (R² = 0.13). The coronal plane coordination allowed to discriminate healthy subjects from all hip OA patients (sensibility = 0.86; specificity = 0.59). Moreover, when comparing OA patients only, coronal plane coordination allows to discriminate patients with indication of surgery from those with no indication of surgery (sensibility = 0.72; specificity = 0.72). Moreover, the pelvis-thorax coordination demonstrated an excellent reliability and a good responsiveness. Conclusion. The changes in the pelvis-thorax coordination might refer to different mechanisms, from analgesia to motor control plasticity, and might be a possible explanation for the weak correlation between structure and symptoms in hip OA patients. Moreover, such parameter might be used as an objective outcome in hip OA clinical trials.